PELAKSANAAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI EVALUASI KINERJA KARYAWAN DI PT. MUSIM MAS PEKANBARU - HERY DIA ANATA BATUBARA (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to determine the implementation of accounting accountability of employee performance atPT. Musim Mas Pekanbaru. The results of the study found that the influence of cost center accountability accounting andrevenue center had a significant effect on performance evaluation. This is because the accounting variable affects theperformance evaluation variable 11.8%, the remaining 88.2% is influenced by other factors. The regression coefficient ofcost center accounting and revenue center is 0.144 cost center, which is positive value and revenue center is 0.299, which ispositive value. The value can be interpreted accounting accountability positively affects the evaluation of performance.Known central thitung value costs 1,436 < 1,806 and Sig value 0.000 < 0.05, the cost center significantly influenced theperformance evaluation and the revenue center was known to be 1,744 < 1,806 and the Sig value was 0.000 < 0.05, so therevenue center had a significant impact on performance evaluation.